2010
DOI: 10.1137/100787659
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Electromagnetic Fields Caused by Interacting Subwavelength Cavities

Abstract: Abstract. This article is devoted to the asymptotic analysis of the electromagnetic fields scattered by a perfectly conducting plane containing two sub-wavelength rectangular cavities. The problem is formulated through an integral equation, and a spectral analysis of the integral operator is performed. Using the generalized Rouché theorem on operator valued functions, it is possible to localize two types of resonances, symmetric and anti-symmetric, in a neighborhood of each zero of some explicit function, asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…By taking the inner product of (3.14) with e 1 and e 2 respectively, it follows that 15) where the matrix M is defined as…”
Section: Asymptotic Expansion Of the Boundary Integral Operatorsmentioning
confidence: 99%
“…By taking the inner product of (3.14) with e 1 and e 2 respectively, it follows that 15) where the matrix M is defined as…”
Section: Asymptotic Expansion Of the Boundary Integral Operatorsmentioning
confidence: 99%
“…The field enhancement at low frequencies has been investigated by the authors in [19], assuming that the wavelength is much larger than the thickness of the slab. We also refer to a closely related problem of scattering by subwavelength cavities in [7,8], where the layer potential techniques and Gohberg-Sigal theory are applied to study the resonances. A nice introduction to these techniques is given in [3].…”
mentioning
confidence: 99%
“…A nice introduction to these techniques is given in [3]. The techniques adopted in this paper for the analysis of resonances share the same spirit as the ones used in [7,8]. However, we avoid the operator version of residue theorem and Gohberg-Sigal theory by reducing the problem to the analysis of ordinary analytic functions.…”
mentioning
confidence: 99%
“…We may begin with simple geometries, where the analytical approaches are made possible to obtain an accurate description of the electromagnetic field. In [7,11], the field enhancement was considered for a single rectangle cavity and double rectangle cavities. Using asymptotic expansions of Green's function, they showed that the limiting Green function is a perfectly conducting plane with a dipole in place of the cavity when the width of the cavity shrinks to zero.…”
Section: Introductionmentioning
confidence: 99%